The Sandman. Vol. 1, Preludes & nocturnes - Gaiman, Neil (Gaiman, Neil. Sandman library, 2018)
"An occultist attempting to capture Death to bargain for eternal life traps her younger brother Dream instead. After his 70 year imprisonment and eventual escape, Dream, also known as Morpheus, goes on a quest for his lost objects of power. On his arduous journey Morpheus encounters Lucifer, John Constantine, and an all-powerful madman. This book also includes the story "The Sound of Her Wings," which introduces us to the pragmatic and perky goth girl Death."--